2017
DOI: 10.4037/ccn2017485
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Families of Intensive Care Unit Patients Regarding Involvement in Delirium-Prevention Activities: A Qualitative Study

Abstract: BACKGROUND Nonpharmacologic delirium-prevention strategies are commonly used in the intensive care unit by bedside nurses. With up to 80% of intensive care unit patients becoming delirious, and lacking treatment options, prevention is key. However, with increasing nurse workloads, innovative delirium-prevention strategies such as involving the patient’s family are needed. OBJECTIVE To gain insight into opinions of patients’ f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(44 citation statements)
references
References 35 publications
4
38
0
2
Order By: Relevance
“…These studies did not focus on any kind of stimulation but focusing on allowing a family presence for a longer time which promote patient family interaction thus maintaining brain stimulation with family members. [22,35,36] The current study findings are in line with these studies as family voice group had a higher mean number of visitors than the two other groups. This can be described as the more family members, the more cognitive stimulation and more alertness thus creating a healing environment.…”
Section: Discussionsupporting
confidence: 90%
“…These studies did not focus on any kind of stimulation but focusing on allowing a family presence for a longer time which promote patient family interaction thus maintaining brain stimulation with family members. [22,35,36] The current study findings are in line with these studies as family voice group had a higher mean number of visitors than the two other groups. This can be described as the more family members, the more cognitive stimulation and more alertness thus creating a healing environment.…”
Section: Discussionsupporting
confidence: 90%
“…12 Herein lies an opportunity for families to participate in delirium prevention, detection, and management. Although previous research has shown that family members of critically ill patients want to assist with nonpharmacological delirium prevention activities, 13,14 most families lack adequate delirium knowledge to be effective partners.…”
Section: Résumémentioning
confidence: 99%
“…33,34 Measures Caregiver ICU Delirium knowledge questionnaire (CIDKQ) A 21-item multiple choice (yes/no/don't know) questionnaire was used to measure family members' knowledge about ICU delirium and to assess the effect of the education provided. The CIDKQ addressed the three dimensions of delirium knowledge: risk factors (items 1-10), actions (items [11][12][13][14][15][16] and symptoms (items 17-21). The CIDKQ score ranges from 0 to 21, with a higher score indicating more ICU delirium knowledge.…”
Section: Interventionmentioning
confidence: 99%
“…Like our study, other studies have found that when patients enter the paediatric intensive care unit, both the young adult patients and their family suffer discomfort, especially related to separation of the patient from the family, and this is one of the main reasons for criticism by young adult patients, along with the loss of the parental referent (33,34). For this reason, it is important that the healthcare professional be open to listening to the patient, evaluating the experience of the patient and the family, and identifying the needs in this regard, given that this affords an opportunity to reduce the anxiety associated with the intensive care unit stay and to boost the physical and emotional comfort of the patient and the family (35)(36)(37). In addition, as the participants in the present study have noted, information and the continuous presence of the family, as a result of increased flexibility in visiting hours, helps reduce the secondary emotional impact brought on by the separation resulting from the hospitalisation and contribute to the well-being of the patient, minimising the traumatic experience of the illness.…”
Section: Discussionmentioning
confidence: 99%